2023
DOI: 10.3390/molecules28031186
|View full text |Cite
|
Sign up to set email alerts
|

A Concise Profile of Gallic Acid—From Its Natural Sources through Biological Properties and Chemical Methods of Determination

Abstract: Nature is a valuable source of anti-oxidants that have a health-promoting effect by inhibiting various undesirable changes leading to cell degradation and, consequently, potential disease ailments. One of them is gallic acid which has been used as a healing agent since ancient times. Currently, due to various beneficial properties, this compound is considered to be one of the main phenolic acids of great importance in numerous industries. It is commonly used as a substance protecting against the harmful effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…In the human diet, gallic acid is commonly present as esters in tea, grapes, mangoes, and edible mushrooms. Recent investigations have demonstrated the antioxidant and anti‐inflammatory effects of gallic acid, shedding light on its potential in treating human diseases such as diabetes, cardiovascular disease, and cancer (Wianowska & Olszowy‐Tomczyk, 2023) (Table 3).…”
Section: Mechanisms Of Polyphenolic Compounds Protect Against Hepatic...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the human diet, gallic acid is commonly present as esters in tea, grapes, mangoes, and edible mushrooms. Recent investigations have demonstrated the antioxidant and anti‐inflammatory effects of gallic acid, shedding light on its potential in treating human diseases such as diabetes, cardiovascular disease, and cancer (Wianowska & Olszowy‐Tomczyk, 2023) (Table 3).…”
Section: Mechanisms Of Polyphenolic Compounds Protect Against Hepatic...mentioning
confidence: 99%
“…In the human diet, gallic acid is commonly present as esters in tea, grapes, mangoes, and edible mushrooms. Recent investigations have demonstrated the antioxidant and anti-inflammatory effects of gallic acid, shedding light on its potential in treating human diseases such as diabetes, cardiovascular disease, and cancer(Wianowska & Olszowy- Tomczyk, 2023) (Table3).Chang et al showed that gallic acid-mediated TNF-α production promoted HSC necroptosis by upregulating the key necrosis regulatory protein TRADD and receptor-interacting protein 3 (RIP3)…”
mentioning
confidence: 99%
“…2 Gallic acid possesses numerous properties of interest such as antioxidant, antibacterial, anticancer, anti-fungal, anti-inammatory, and anti-viral properties. 1 Due to its properties, gallic acid can be used in the pharmaceutical industry to prevent oxidative damage in biomolecules by scavenging the reactive oxygen species (ROS) and preventing the development and progression of various cancer cells. It can also be used as a remoter astringent in cases of internal hemorrhage, to treat albuminuria, diabetes, psoriasis, and external hemorrhoids as well as to prevent excessive inammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…grapes and tea) as well as in foods and beverages. 1 It is often used as a standard reference for the quantification of polyphenols ( e.g. in the Folin & Ciocalteu assay).…”
Section: Introductionmentioning
confidence: 99%
“…GA comprises a benzene ring with three adjacent hydroxyl groups and one carboxylic group at the 1 position [ 16 ]. GA exhibits strong antioxidant activity [ 16 , 17 ] and possesses anti-cancer, anti-inflammatory, anti-microbial, and anti-fungal properties [ 18 ]. Therefore, the biological and pharmacological properties of GA have attracted the attention of researchers by attempting to improve its activity by combining it with other bioactive ingredients.…”
Section: Introductionmentioning
confidence: 99%